2015
DOI: 10.1038/srep15103
|View full text |Cite
|
Sign up to set email alerts
|

Interface designed MoS2/GaAs heterostructure solar cell with sandwich stacked hexagonal boron nitride

Abstract: MoS2 is a layered two-dimensional semiconductor with a direct band gap of 1.8 eV. The MoS2/bulk semiconductor system offers a new platform for solar cell device design. Different from the conventional bulk p-n junctions, in the MoS2/bulk semiconductor heterostructure, static charge transfer shifts the Fermi level of MoS2 toward that of bulk semiconductor, lowering the barrier height of the formed junction. Herein, we introduce hexagonal boron nitride (h-BN) into MoS2/GaAs heterostructure to suppress the static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 39 publications
3
79
0
Order By: Relevance
“…Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works. low-dimensional materials, which, apart from the insights from the scientific point-of-view, suggest possible novel applications of two-dimensional TMDs in thin and flexible optoelectronic devices, such as photodiodes [10,11] and photodetectors [12], single-photon emitters [13][14][15] or in spin-and valleytronic devices [16]. However, their quasi-2D nature is a double-edged sword in the sense that the low thickness limits the absorption efficiency and optical quantum yields of the TMD materials.…”
Section: Introductionmentioning
confidence: 99%
“…Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works. low-dimensional materials, which, apart from the insights from the scientific point-of-view, suggest possible novel applications of two-dimensional TMDs in thin and flexible optoelectronic devices, such as photodiodes [10,11] and photodetectors [12], single-photon emitters [13][14][15] or in spin-and valleytronic devices [16]. However, their quasi-2D nature is a double-edged sword in the sense that the low thickness limits the absorption efficiency and optical quantum yields of the TMD materials.…”
Section: Introductionmentioning
confidence: 99%
“…The monolayer MoS 2 itself is too thin to absorb enough incoming light. In the previous paper, we have designed MoS 2 /GaAs solar cells with a power conversion efficiency over 9.03% [35], which utilizes the good optoelectronic characteristics and high carrier mobility of GaAs [36][37][38]. In this communication, we design a simple and high performance …”
Section: Introductionmentioning
confidence: 99%
“…The presence of the obvious band gap allows the fabrication of the MoS 2 transistors with an on/off ratio exceeding 10 8 and the photodetectors with high responsivity [7, 8]. Recently, MoS 2 combined with other semiconductors has attracted much interest, such as GaAs, Si, and GaN [913]. These designed heterostructures supply feasible technical route for MoS 2 -based materials to develop practically applicable optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Among all these bulk semiconductors, GaAs has a suitable direct band gap of ~ 1.42 eV and high electron mobility (~ 8000 cm 2  V −1  s −1 ). Lin et al fabricated MoS 2 /GaAs solar cells with a power conversion efficiency over 9.03% [9]. Further, Xu et al reported a MoS 2 /GaAs self-driven photodetector with the extremely high detectivity of 3.5 × 10 13  Jones [10].…”
Section: Introductionmentioning
confidence: 99%